2015
DOI: 10.1111/acem.12586
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Transfers and Transfer Relationships in United States Hospitals

Abstract: Objectives: The objective was to describe transfers out of hospital-based emergency departments (EDs) in the United States and to identify different characteristics of sending and receiving hospitals, travel distance during transfer, disposition on arrival to the second hospital, and median number of transfer partners among sending hospitals.Methods: Emergency department records were linked at transferring hospitals to ED and inpatient records at receiving hospitals in nine U.S. states using the 2010 Healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 19 publications
2
52
1
1
Order By: Relevance
“…Findings of this study that assessment of patients with mechanisms of acute trauma are a common cause of preventable transfer is consistent with previous reports. Among injured patients in a single trauma centre, 2000 patients per year were transferred and subsequently discharged from the second ED . Suspected traumatic spinal injuries, particularly of the cervical spine, are often transferred to tertiary trauma centres from other hospitals and subsequently discharged from the trauma centre's ED suggesting secondary over‐triage of such injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of this study that assessment of patients with mechanisms of acute trauma are a common cause of preventable transfer is consistent with previous reports. Among injured patients in a single trauma centre, 2000 patients per year were transferred and subsequently discharged from the second ED . Suspected traumatic spinal injuries, particularly of the cervical spine, are often transferred to tertiary trauma centres from other hospitals and subsequently discharged from the trauma centre's ED suggesting secondary over‐triage of such injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, it has been reported that on average 8% of transferred patients were discharged after ED evaluation in the second hospital and a substantial proportion had short length of stays. Certain disease categories had significantly higher post‐transfer ED discharge rates, including acute trauma (13%) …”
Section: Introductionmentioning
confidence: 99%
“…We used the Healthcare Cost and Utilization Project State Emergency Department Databases and State Inpatient Databases for 2010. A full explanation on how states were chosen, how ED transfer records were linked to inpatient or ED records at the receiving hospital, and how the study population was identified is elsewhere in this issue …”
Section: Methodsmentioning
confidence: 99%
“…In this issue of Academic of Emergency Medicine , two articles by Kindermann et al . provide the first comprehensive understanding of ED transfer patterns in the United States by taking advantage of this powerful AHRQ data from nine states.…”
mentioning
confidence: 99%
“…In their study on ED transfer patterns, Kindermann et al. describe the variation in ED transfer rates for the most commonly transferred conditions, the characteristics of sending and receiving hospitals, the distances of transfer, the numbers of hospitals EDs transfer to, and the ultimate dispositions of patients transferred.…”
mentioning
confidence: 99%